Intervención en duelo y mindfulness (2021)
This study assesses the effect of and Minfulness Emotional Intelligence Program (PINEP) intervention on adults who have suffered the loss of a loved one. The intervention lasts twelve sessions, two and a half hours per week. The sample is made up of 17 adults from an age range of between 26 y 71 años (M= 50.59; SD= 14.44). Participants who complete the interventión show greater tolerance to discomfort, developing skill in mindfulness [t(16) =4.17, d= 1.04, p ≤ .001], and a decrease in state anxiety [t(16)= -2.94, d= .72, p= .005], trait anxiety [t(16)= -3.48, d= .78, p ≤ .001] and depression [t(16)= -3.18, d= .66, p= .003].